TEMBANG JAWA DALAM BUDAYA POPULER: ANALISIS ISI KIDUNG JAWA MODERN SINDY PURBAWATI - Mad Yahya; Wiwik Retno Handayani (Universitas Muhammadiyah Surakarta, 2023)
This article aims to analyze the aspects of language uniqueness in Kidung Jawa Modern. The data is eleven modern Javanese kidung released by Sindy Purbawati. The data was collected using the note-taking technique. Furthermore, content analysis is used to identify language uniqueness in kidung. Moreover, the data was analyzed using Jakobson's six linguistic functions to reveal the categories of literary language functions in the kidung. The study results show that Kidung Jawa Modern tends towards lexical repetition and synonymous semantic repetition. Based on the language uniqueness of these linguistic aspects, the author groups the themes of kidung discourse into four categories (1) religiosity, (2) social and romantic, (3) ecological, and (4) educative. Based on the content analysis approach, the language uniqueness of the kidung in the lexical form are the repetition of possessive pronouns in social romance-themed kidung, personal pronouns in religious-themed kidung, and the third person pronoun in educational-themed kidung. In the semantic aspect, the repetition of synonyms is found in kidung with ecological themes that relate to synonyms of natural terms, the songs of romance that relate to synonyms of heart and mood, and the songs with religious themes that relate to the repetition of synonyms of divine terms. The interest of people in Javanese kidung in Kidung Jawa Modern is related to the poetic aspects of the kidung, variations in discourse themes, and the relevance of the kidung to the nature and social phenomena that occurred in society when the kidung was released.Keywords: Javanesse kidung, content analysis, Kidung Jawa Modern, and popular culture